EFFECT OF DIFFERENT FERTILIZER LEVELS OF (CHEMICAL AND ORGANIC) ON THE YIELD OF THYME ( Thymus vulgaris ) - Abdul Jabbar Al-Hubaity; Mohammed D. AL-Sawaf; Mothafer A. AL-Mosuly (Mesopotamia Journal of Agriculture)
The Thyme transplants were grown in pots containing 3 Kg. weight of sandy soil in the greenhouse, to study six fertilizer treatments (Chemical + Organic) as follows: (0.0% + 100%), (25% + 75%), (50% + 50%), (75% + 25%), (100% + 0.0%), (0.0% + 0.0%), Sheep manure was applied as a source of organic fertilizer in addition to the available chemical fertilizer. At the end of the experiment the following traits were measured plant height (cm), fresh and dry weight of the vegetative growth (gm), number of branches, % of flowering plants and chlorophyll %, N%, P%, K%, of the vegetative growth, in addition to the physical properties of oil viz., oil %, density of oil mg/ml, specific gravity and refractive index. The results revealed that the second and forth treatments (Chemical + Organic) (25% + 75%), (75% + 25%) were the best in most traits, whereas, the first treatment (0.0% + 100%) was superior in oil %, while the third treatment  (50% + 50%) was distinguished in the physical properties of oil viz., density of oil, specific gravity and refraction index.